A taxonomic review of Poblicia Stål, 1866 (Hemiptera: Fulgoromorpha: Fulgoridae), with special reference to species north of Mexico - Bartlett, Charles R.; Hagerty, Tyler; Yanega, Douglas; Hoddle, Mark S.; Gebiola, Marco; Gómez-Marco, Francesc (Zootaxa, 2025)
The species of Poblicia Stål, 1866, here given the appellation speckled lanternflies, are reviewed with particular attention to species found north of Mexico. The genus Poblicia at this time consists of four species: the type species P. misella (Stål, 1863) (from Mexico), P. fuliginosa (Olivier, 1791) (from eastern USA), and two species removed from synonymy—P. thanatophana Kirkaldy, 1907 (western USA) and P. cribrata Gerstaecker, 1860 (locality uncertain). Amended diagnoses are provided for these Poblicia species. Life history and molecular sequence data (28S, ITS2 and CO1) are discussed to support the designation of P. fuliginosa and P. thanatophana as separate species. Poblicia texana is established as the type species for the new genus Angulapteryx gen. nov. as Angulapteryx texana comb. nov.